Patients’ and clinicians’ views on the optimum schedules for self-monitoring of blood pressure - McManus, R; Grant, S; Hodgkinson, J; Milner, S; Martin, U; Tompson, A; Hobbs, F; Mant, J; Greenfield, S (Royal College of General Practitioners, 2016)
Background Self-monitoring of blood pressure is common but guidance on how it should be carried out varies and it is currently unclear how such guidance is viewed. Aim To explore patients’ and health care professionals’ (HCPs) views and experiences of the use of different self-monitoring regimes, to determine what is acceptable and feasible and to inform future recommendations. Design and Setting Thirteen focus groups plus four HCP interviews were held, total of 66 participants (41 patients, 25 HCPs) from primary and secondary care with and without experience of self-monitoring. Method Both standard and shortened self-monitoring protocols were considered. Focus groups and interviews were recorded, transcribed verbatim and analysed by constant comparative method. Results Patients generally supported structured schedules but with sufficient flexibility to allow adaptation to individual routine. They preferred a shorter (3-day) schedule to longer (7-day) regimes. Whilst HCPs could describe benefits for patients of using a schedule, they were reluctant to recommend a specific schedule. Concerns surrounded the use of different schedules for diagnosis and subsequent monitoring. Appropriate education was seen as vital by all participants to enable a self-monitoring schedule to be followed at home. Conclusions There is not a ‘one size fits all approach’ to developing the optimum protocol from the perspective of users and those implementing it. An approach whereby patients are asked to complete the minimum number of readings required for accurate BP estimation in a flexible manner seems most likely to succeed. Informative advice and guidance should incorporate such flexibility for patients and professionals alike.